Study of chemical and microbial characteristics of camel raw milk and identification of dominant flora of lactic acid bacteria by PCR method in Semnan - M. Parsaeimehr (Bihdāsht-i Mavādd-i Ghaz̠āyī, 2019)
Camel milk is considered as the most important sources of nutrition in terms of protein, vitamins and minerals, which is important for health. The aim of this study was to evaluate the chemical properties, microbial profile and the presence of lactic acid bacteria in camel milk. In this study, 24 samples of camel milk from Semnan's livestock farms were collected randomly in a month and were taken to the Food Health Laboratory under aseptic condition and then analyzed for chemical and microbial characterization. The percentage of protein, pH and fat percentage are in the range of 1 to 3 percent, 6 to 6.6 and 2 to 3.5 percent respectively. The average logarithm number of aerobic bacteria, enterococcus, micrococcus, aerobic and anaerobic lactic acid bacteria and mold and yeast were 6.08± 0/06, 3/66± .072, 4.14± 0.06, 5/24± 0.42, 5.18± 0.35, 3/84± 1.15 log cfu g-1, respectively. It should be noted that coliform and Enterobacteriaceae were not isolated from any of the camel milk samples. Staphylococcus aureus was isolated from 2.78 to 4.49 cfu log g-1. In addition, identification of isolates of lactic acid bacteria was performed by sequencing of 16s rDNA. Accordingly, the isolates belong to Lactobacillus casei, Lactobacillus pasturianus, Enterococcus faecium and Enterococcus faecalis. The results of this study showed the microbial diversity in camel milk.